2000
DOI: 10.1109/55.887476
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of RuO2 gate electrodes for dual metal gate Si-CMOS

Abstract: The rutile stoichiometric phase of RuO 2 , deposited via reactive sputtering, was evaluated as a gate electrode for Si-PMOS devices. Thermal and chemical stability of the electrodes was studied at annealing temperatures of 400 C and 600 C in N 2 . X-ray diffraction patterns were measured to study grain structure and interface reactions. Very low resistivity values were observed and were found to be a strong function of temperature. Electrical properties were evaluated on MOS capacitors, which indicated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…23-25 and 34-38͒ and even that of RuO 2 ͑5.0− 5.3 eV͒. [35][36][37][38][39][40][41][42] However, the large WF shift corresponds very well with Nabatame et al's report, 22 which shows a V fb shift of ϳ1 V for both Ru/ SiO 2 and Ru/ HfO 2 gated stacks after thermal treatment in O 2 .…”
Section: E Dependence On the Type Of Dielectricssupporting
confidence: 72%
“…23-25 and 34-38͒ and even that of RuO 2 ͑5.0− 5.3 eV͒. [35][36][37][38][39][40][41][42] However, the large WF shift corresponds very well with Nabatame et al's report, 22 which shows a V fb shift of ϳ1 V for both Ru/ SiO 2 and Ru/ HfO 2 gated stacks after thermal treatment in O 2 .…”
Section: E Dependence On the Type Of Dielectricssupporting
confidence: 72%
“…9,10 As an alternative gate electrode for integration with high-ZrO 2 and Zr silicate dielectrics in PMOS devices, excellent stability and electric properties indicated that RuO 2 is a promising candidate for implementation in PMOS devices. 11,12 However, detailed information on the work function of conductive oxides relating to the oxidation state is very limited. 13 When integrating them with alternative high-dielectrics, the unknown band alignment may result in unpredictable electrical properties.…”
mentioning
confidence: 99%
“…They can offer some unique features such as a wide range of available work functions, high density of states around the Fermi level, and small energy perturbation due to carrier confinement, further improving memory performance. 5 Among various metal materials, ruthenium (Ru) has been studied for applications of dynamic random-access memory (DRAM), ferroelectric random-access memory (FeRAM), and complementary metal-oxide-semiconductor (CMOS) technology, [6][7][8] exhibiting good compatibility with current semiconductor technology; for example, it has high chemical and thermal stability (not easily diffused), simple dry etching capability, and good electrical conductivity even when oxidized. Furthermore, the high work function of Ru (4.71 eV) allows for creation of deeper potential wells for charge storage, which gives rise to better retention and charging characteristics.…”
Section: Introductionmentioning
confidence: 99%